VISITOR GUIDE APPLICATION AT MUSEUM WITH AUGMENTED REALITY ANDROID-BASED - Yunita Dwi Cahaya; Ali Ikhwan; Adnan Buyung Nasution (Department of Computer Engineering, Universitas Wiralodra, 2023)
Study this aim as a spatial introduction media on each the floor of the museum and the collections of the Regional Museum of Deli Serdang Pada Visitors Android based . Study this conducted at the Regional Museum of Deli Serdang, which is located at Jalan Negara, Petapahan Sports , Arts and Culture Area , Lubuk Pakam , Deli Serdang, North Sumatra 20517. In research this writer use Research and Development (R&D) methods . Study it also uses Rapid Application Development (RAD) as methodology development application . In conclusion this that the Visitor Guide Application (VGA) with technology Augemented Reality at the Regional Museum of Deli Serdang based on Android has built use Unity 3d apps , Blender and Vuforia with attractive appearance and user friendly. Augmented reality technology can used as tool guide because capable displays 3d object on each collection . The Visitor Guide Application (VGA) is also used as an introduction to spatial planning in each area the floor of the museum and collections in the Deli Serdang Regional Museum visitors Android based . Application this aim for make it easy visitors and the museum in the introduction process collections at the Regional Museum of Deli Serdang.